Assessing China's development in the global economy: underdevelopment, uneven and combined development or developmental catch-up? - Lee, Pei May (2019)
The purpose of this research is to examine the complex debates surrounding Chinese development. Although China has displayed impressive economic figures throughout its reform period, an argument remains as to whether the double-digit rates of growth reflect a broader phenomenon of development. Furthermore, the question of which development model China subscribes to is widely disputed within the scholarly literature. While there is clearly no lack of academic research concerning Chinese development, in this project I will propose a comparative analysis of the competing theoretical perspectives to understanding the Chinese political economy. The unresolved debates, which formed the key research questions, can be assessed in a more systematic and comprehensive manner using the proposed approach. This thesis therefore offers an analysis of the Chinese development through the lenses of four relevant theories of development: 1) Modernisation Theory, 2) Developmental State Theory, 3) Dependency Theory and 4) Theory of Uneven and Combined Development. Using these theories, this thesis seeks to answer two key questions derived from the complex debates surrounding Chinese development: 1) Can China catch up? And 2) What is the particular development model of China? As the primary type of data required to answer the research questions is macro-level data, document analysis has been employed where this thesis triangulates facts and figures derived from Chinese governmental bodies, international institutions as well as key scholarly literature. This research has also engaged extensively with the database of the World Bank for a comparison of Chinese development with developing and developed economies. The analysis concludes that substantial progress has been achieved by China on its path of catch-up with developed economies, with potential for complete developmental catch-up. The analysis also confirms that the developmental outcomes were achieved through the adoption of East Asian Development Model. In sum, the theoretical and empirical assessments of the two main key debates conclude that Chinese political economy is state-led modernisation and uneven and combined.